A novel approach to evaluate the pharmacodynamics of a selective dopamine D1/D5 receptor partial agonist (PF-06412562) in patients with stable schizophrenia. (October 2019) - Arce, Estibaliz; Balice-Gordon, Rita; Duvvuri, Sridhar; Naylor, Melissa; Xie, Zhiyong; Harel, Brian; Kozak, Rouba; Gray, David L; DeMartinis, Nicholas
Background: PF-06412562 is an orally bioavailable, selective dopamine D1/D5 receptor partial agonist with a non-catechol structure under evaluation for treatment of cognitive impairment in schizophrenia. Aims: This randomized, double-blind, placebo-controlled, parallel-group, Phase 1b study examined the pharmacokinetics and pharmacodynamics of three doses of PF-06412562 (3 mg, 9 mg, and 45 mg twice daily) over 15 days in patients with schizophrenia receiving antipsychotics. Methods: Primary endpoints included adjunctive safety/tolerability and effects on MATRICS Consensus Cognitive Battery Working Memory domain and reward processing (Monetary Incentive Delay) tasks. Exploratory endpoints included other behavioral/neurophysiological tasks, including the N-back task. Results: Among 95 subjects (78% male; mean age 34.8 years), baseline characteristics were similar across groups. The MATRICS Consensus Cognitive Battery Working Memory composite change from baseline on Day 13 improved in all groups, the smallest improvement was observed in the 45 mg group and was significantly smaller than that in the placebo group (two-sided p =0.038). For the Monetary Incentive Delay task (change from baseline in blood-oxygen-level-dependent functional magnetic resonance imaging activation in anterior ventral striatum for the contrast of cue gain>cue no gain on Day 15), no PF-06412562 dose was significantly different from placebo. No doses of PF-06412562 showed a significant difference on two-back task accuracy versus placebo. Conclusions: Adjunctive treatment with PF-06412562 was safe and well tolerated in patients with schizophrenia. PF-06412562 failed to show clinical benefit relative to placebo on assessments of cognition or reward processing in symptomatically stable patients over a 15-day treatment period. Numerous limitations due to the safety study design warrant further efficacy evaluation for this drug mechanism.